Mental Health, Emotional Intelligence, and Self-Esteem in Athletes and Non-Athletes: A Comparative Study (Jagannath University Journal of Science, 2025)
Involvement in sports and other physical pursuits might be more advantageous for student-athletes in terms of their mental, emotional, and social development than their non-athlete peers. This study examined the differences in mental health, emotional intelligence, and self-esteem between athletes and non-athletes among university students. A total of 294 participants (147 athletes and 147 non-athletes) were recruited through the convenience sampling technique. Data collection involved the Bangla version of the General Health Questionnaire (GHQ-12), Emotional Intelligence Scale, and Self-Esteem Scale. Data were analyzed using Pearson product-moment correlation, t-test, and hierarchical regression. Pearson product-moment correlation analysis revealed a strong negative interconnection between emotional intelligence and mental health problems within both groups. Findings indicated that athletes reported significantly lower mental health problems as compared to non-athletes. Conversely, athletes exhibited significantly higher emotional intelligence and self-esteem than their non-athlete counterparts. Hierarchical regression analysis showed that emotional intelligence significantly predicted mental health for athletes and non-athletes, while self-esteem showed no significant impact. The findings expressed a crucial role of emotional intelligence in mental health. It also highlights the implications of interventions to enhance emotional intelligence in athletic and non-athletic populations.Jagannath University Journal of Science, Volume 11, Number 2, Dec. 2024, pp. 35−44